Gallbladder Torsion: A Diagnostic Challenge - Sharon Gabizon; Kimberley Bradshaw; Eshwarshanker Jeyarajan; Rafid Alzubaidy; Victor Liew (Case Reports in Surgery)
80-year-old female presented with clinical findings suggestive of acute cholecystitis. Intraoperatively we discovered a dusky gallbladder with gangrenous patches and gallbladder torsion with 270 degrees clockwise rotation along the longitudinal axis. Gallbladder torsion is a rare cause of acute cholecystitis with less than 500 cases published in the literature. Gallbladder torsion should be included in the list of differential diagnoses in patients suspected of having acute cholecystitis especially when there are inconsistencies between clinical features and imaging. It is worth noting that 3-dimensional reconstructed CT may be useful in preoperative diagnosis of gallbladder torsion.